Circumcision Law in Christianity and Islam - M Ikhsan Tanggok (Universitas Islam Negeri Jakarta, 2018)
For Muslims around the world, circumcision a common tradition that has been passed down from generation to generation. If their child is not circumcised, Muslim parents feel guilty for not fulfilling their religious duties. The Muslim practice of circumcision follows the tradition of the Prophet Abraham, not the prophet Muhammad. Unlike the Quran, the performance of circumcision is instructed by the Bible, but there are both some Christians who do it and some who do not. They disagree about the law surrounding circumcision described in the Bible. The messengers mentioned in the Bible also have different views about it, some believing it is mandatory and others not. For this reason, some Christians perform circumcision because of their awareness of its connection to bodily health and others to obey the teachings of Jesus; meanwhile, some do not carry out the messengers' orders because of their different interpretations of them.